Phenotypes and survival in Erdheim‐Chester disease: Results from a 165‐patient cohort - F. Cohen Aubart; Jean‐François Emile; Fabrice Carrat; Zofia Hélias‐Rodzewicz; Valérie Taly; Frédéric Charlotte; Philippe Cluzel; Jean Donadieu; Ahmed Idbaïh; Stéphane Barète; Zahir Amoura; Julien Haroche (2018)
Erdheim-Chester disease (ECD) is a multi-systemic non-Langerhans cell histiocytosis that is characterized by tissue infiltration of foamy histiocytes.1-3 Following the discovery that 60 to 100% of ECD patients carry the BRAFV600E mutation, ECD was recently re-classified as an inflammatory myeloid neoplasm.4-6 The phenotype and clinical course of ECD are heterogeneous, ranging from asymptomatic to life-threatening multi-organ involvement.7 Previous studies report that CNS involvement and interferon-alpha treatment are independent predictors of survival of ECD.8 However, even though interferon (IFN)-α, anakinra, infliximab, and cladribine9 are largely used to treat ECD, BRAF targeting treatments are increasingly prescribed.10 We aimed to determine the phenotype of BRAF-mutated ECD patients and analyze the factors associated with survival in the era of BRAF genotyping. The present study relies on a cohort of 165 ECD patients seen at least once in a French tertiary center between 1981 and 2016. In all cases, the ECD diagnosis was based on a typical clinical and radiological presentation and histological findings that were centrally reviewed by F.C. or J.F.E.3 The study was approved by the ethics committee Comité de Protection des Personnes Ile de France III (#2011-A00447-34) and was conducted in accordance with the Declaration of Helsinki. All the patients underwent BRAF mutation detection on codon V600 by pyrosequencing as previously described.4 All cases without mutation by pyrosequencing were then analyzed by multiplex picodroplet digital PCR as previously described.11 The total amount and quality of the tumor DNA available was limited; however, 85% of the samples that were considered negative for BRAF mutations had at least 1000 native copies of the BRAF codon V600 amplified. Cardiac and CNS involvements were previously defined.8 The follow-up ended in June 2016. Differences between the groups were tested using the Mann–Whitney test for the continuous data and Fisher's exact test for the qualitative data. Logistic regression models were used to identify factors associated with BRAF status. All of the predictors significantly associated with BRAF status in the univariate models were entered in a multivariate model. Survival curves were built using the Kaplan-Meier method considering the time of diagnosis of ECD to death or last follow-up. Cox proportional hazard regression models were used to identify predictors of survival. The multivariate Cox model included sex and age (as adjustment covariates), BRAF status, targeted therapy (because we hypothesized that they could be prognostic factors), IFN-α or PEGylated-IFN-α and CNS (as previously known prognostic factors8) and other significant predictors identified in univariate Cox models. All of the tests were two-sided, and a P-value < .05 was considered statistically significant. Statistical analyses were performed using the GraphPad Prism V 6.0 (GraphPad software, La Jolla, California) and SAS v 9.4 (SAS institute Inc, Cary, North Carolina). The demographic and clinical characteristics of the 165 patients are presented in Table 1. The BRAF status was determined in 133 patients. For 32 patients, the DNA quality was no sufficient to conclude. Eighty-eight patients (66%) had a BRAFV600E mutation. Comparisons between the BRAFV600E and wild-type (WT) patients showed that the BRAFV600E patients had more cardiac and cerebellar involvement, more diabetes insipidus and more retro-orbital infiltration (Table 1). Regarding heart involvement, cardiac right atrial pseudotumor was the cardiac localization that was the most closely linked to BRAF status (univariate odds ratio (OR) 14.81, 95% confidence interval (95% CI) 4.87-44.97, P < .0001). For the multivariate analysis, all of these factors remained significantly associated with BRAFV600E, and the multivariate adjusted ORs were 10.81 (95% CI 4.21–27.76) for cardiac involvement, 10.63 (95% CI 2.02; 56.02) for cerebellar involvement, 3.67 (95% CI 1.17-11.54) for diabetes insipidus, and 4.06 (95% CI 1.18-14.00) for retro-orbital infiltration. The mean follow-up was 63 months (SD 55 months); 56 months in the BRAFV600E mutated group and 63 months in the WT group. The treatments and survival with respect to BRAF status are presented in Table 1. The overall mortality was 24.8%, with a median survival of 162 months. The 5-year survival was 82.7%. Fifty-six patients (34%) were treated with targeted therapy (BRAF or MEK inhibitor). The treatments did not differ between the BRAFV600E and WT patients except for the targeted therapy, which was more frequently used in the BRAFV600E patients (P < .0001). The univariate and multivariate analyses of survival are detailed in Table 2. Factors associated with a poor survival in ECD were retroperitoneal (OR 3.85, 95% CI 1.68-8.83) and lung involvement (OR 2.74 95% CI 1.38-5.43). CNS involvement, which was linked to the BRAF status, was also associated with worse survival (OR 2.62, 95% CI 1.28-5.37). Treatments with IFN-α (OR 0.38, 95% CI 0.16-0.89) and targeted therapies (OR 0.33, 95% CI 0.11-0.93) were associated with a better survival. ECD is a heterogeneous disease of variable prognosis.3, 6-8 In this study, we identified a cardiac phenotype closely linked to the BRAF status mainly characterized by atrial pseudotumor. CNS involvement was also associated with BRAFV00E mutation, as previously reported.8 The physiopathology of the close link between right atrial pseudotumor and the BRAFV600E mutation remains unclear. However, the right atrium is known to carry cardiac atrial appendage stem cells, and we can hypothesize that they derive from medullar progenitors in a dynamic manner so that a somatic mutation might be found in these cells. In this series, BRAF status was not an independent prognosis factor. The 3 main independent phenotypic features associated with a worse survival were CNS, retroperitoneal and lung involvements. Moreover, IFN-α and targeted therapies improved the survival of the ECD patients. Even if there is increasing evidence that targeted therapies are useful in ECD,10, 12-14 this is the first demonstration that such treatments improve survival in this disease. To explain why the BRAF status was not identified as an independent factor for survival, we can highlight the fact that BRAF status was closely linked to heart and CNS involvement. It is probable that targeted therapies were more frequently used in such patients and this may have interfered with the survival of the patients with mutated BRAF. Our study has several limitations. First, only the BRAFV600E status was identified in most of the patients. Analyses of other kinase alterations in BRAF or other genes were not routinely obtained in a sufficient number of patients to draw some conclusions about other genotype/phenotype correlations. Another limitation was the determination of the BRAF status in only 133/165 patients (81%). This percentage was higher in more recently diagnosed patients.11 As the management of ECD patients dramatically changed during the last decade, this could have led to biases in the results. In conclusion, we identified a cardiac and neurological phenotype associated with BRAF status in ECD. Cardiac involvement in BRAF mutated patients is characterized by large vessels involvement and atrial pseudotumor. Targeted therapies might improve the prognosis of such patients. None of the authors have conflict of interest to disclose. This work was not supported by any funding. Fleur Cohen-Aubart, Jean-François Emile, Zahir Amoura, and Julien Haroche designed the study. Fleur Cohen-Aubart, Jean-François Emile, Frédéric Charlotte, Philippe Cluzel, and Julien Haroche collected the data. Jean-François Emile and Frédéric Charlotte centrally reviewed the histological samples. Jean-François Emile, Zofia Helias-Rodzewicz, and Valérie Taly determined the BRAF status. Philippe Cluzel reviewed the cardiovascular imaging. Fleur Cohen-Aubart and Fabrice Carrat conducted the statistical analysis. Fleur Cohen-Aubart, Jean-François Emile, Fabrice Carrat, Frédéric Charlotte, Stéphane Barete, Ahmed Idbaih, Jean Donadieu, Zahir Amoura, and Julien Haroche analyzed and interpreted the data. Fleur Cohen-Aubart, Jean-François Emile, Fabrice Carrat, Zahir Amoura, and Julien Haroche wrote the manuscript. All authors critically reviewed and approved the final version of the manuscript.